Collagen hemostat significantly reduces time to hemostasis compared with cellulose: COBBANA, a single-center, randomized trial - Qerimi, Bekim; Baumann, Petra; Hüsing, Johannes; Knaebel, Hanns-Peter; Schumacher, Hardy (The American journal of surgery, 2013)
Background - This single-center, randomized trial compares the hemostatic effectiveness of microfibrillar collagen and oxidized cellulose in arterial bypass surgery. - Methods - In patients undergoing arterial bypass surgery, 2 hemostats, microfibrillar collagen and oxidized cellulose, were randomly used to achieve hemostasis. The primary endpoint was the time to hemostasis. The secondary endpoints were the complication rate, mortality, number of hemostats required, handling, and adhesion. - Results - Collagen achieved hemostasis significantly faster than cellulose, with considerably less hemostats. In addition, its ease of use was rated substantially better. - Conclusion - In arterial bypass surgery, microfibrillar collagen is more effective than oxidized cellulose in achieving hemostasis.
Gesehen am 10.12.2021